Central systolic blood pressure is associated with ethnicity and cardiovascular disease risk factors in Chinese middle-aged population. (29th August 2020) - Wang, Zengwu; Hao, Guang; Zhang, Linfeng; Chen, Zuo; Wang, Xin; Guo, Min; Tian, Ye; Shao, Lan; Zhu, Manlu
Abstract: Background: Central systolic blood pressure (CSBP) is a useful prognostic aid in the reduction and prevention of cardiovascular diseases. However, data regarding the distribution of CSBP in China are not available. The study aimed at assessing the distribution of CSBP and examining its relationship with potential cardiovascular risk factors in the Chinese middle-aged population. Design: A cross-sectional study. Methods: A cross-sectional survey on cardiovascular risk factors across China was conducted in 2009–2010. CSBP levels were estimated using the non-invasive BPro device with A-Pulse central aortic systolic pressure software. The study population included 9113 individuals (mean age 49.84 years; 53.37% women). Results: The CSBP levels (mean (standard deviation)) were 119.46 (17.51) mmHg in men and 119.81 (19.29) mmHg in women. CSBP levels were higher in rural than urban and lower in the southern than the northern populations (both P  < 0.05). The Han ethnic group had higher CSBP levels than the Tibetans ( P  < 0.05) but similar to those in the Mongolian, Uyghur, Kazak and Akha groups. Irrespective of gender, the mean CSBP level was higher in individuals with diabetes and hypertension than in those without these disorders ( P  < 0.05). CSBP was positively associated with cardiovascular risk factors such as age, female gender, body mass index, systolic and diastolic blood pressure, and negatively associated with heart rate. Conclusions: CSBP estimated using the BPro device correlates with various cardiovascular risk factors. Our results may help establish future reference values in the Chinese middle-aged population.